Effectiveness of Pumpkin Seed (Cucurbita moschata) Extract in Reducing Premenstrual Syndrome Symptoms in Adolescent Girls - Eka Apriadi Farkhati Nafi'ah; Sri Sumarn; Sri Endang Windiarti (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2026)
Premenstrual Syndrome (PMS) is a common condition among adolescent girls, characterized by physical and emotional complaints that can interfere with daily activities. In Indonesia, the prevalence of PMS is reported to reach approximately 85% among women of reproductive age, with 60–75% experiencing moderate to severe PMS. This study aimed to evaluate the effectiveness of pumpkin seed extract (Cucurbita moschata) in reducing PMS symptoms in adolescent girls. A quantitative approach was applied using a true experimental design with a pre-test and post-test control group design. The study population consisted of adolescent girls experiencing PMS in the Poltekkes Kemenkes Semarang area. A total of 42 respondents were selected using randomized clinical trial sampling and divided into three groups: intervention 1 (pumpkin seed extract 500 mg, twice daily), intervention 2 (500 mg, once daily), and a control group receiving 500 mg amylum tablets once daily for 10 days. The results showed that administration of pumpkin seed extract at a dose of 500 mg twice daily for 10 days produced the most significant reduction in PMS symptoms (p = 0.000; mean = 23.07). Pumpkin seed extract has potential as an effective natural therapy to alleviate PMS symptoms in adolescent girls.